Collaboration Skills in Vocational Schools in The Information and Communication Technology (ICT) Sector - Kusuma, Hanif Aulia; Yoto, Yoto (BRILIANT: Jurnal Riset dan Konseptual, 2024)
In 2018, the technology, business and ICT (information and communication technology) sectors were the sectors that received the most new students at the vocational school level. Jobs in the ICT sector are one of the sectors that are really needed in Indonesia. There are more job vacancies in the ICT sector for vocational schools than for high schools. However, in the 2015-2019 period, the number of ICT sector workers with high school graduates was higher than vocational school graduates. The soft skill that is most needed in ICT sector jobs is collaboration. The main objective of this literacy study is to describe learning methods to improve collaboration skills in vocational high school students in the ICT field. Systematic literacy study using the PICOC framework is the method used. The results of this literacy study are in the form of descriptions related to: 1. The concept of collaboration; 2. Challenges and obstacles; 3. Learning activities to improve collaboration skills. It was found that problem-based learning (PBL) can improve collaboration abilities. To be suited to the world of work, it is necessary to integrate the Scrum model to develop vocational school students' collaboration skills in the field of ICT.